Beyond the community in participatory forest management: A governance network perspective. (September 2020) - Friedman, Rachel S.; Guerrero, Angela M.; McAllister, Ryan R.J.; Rhodes, Jonathan R.; Santika, Truly; Budiharta, Sugeng; Indrawan, Tito; Hutabarat, Joseph A.; Kusworo, Ahmad; Yogaswara, Herry; Meijaard, Erik; St. John, Freya A.V.; et al.
Highlights: Community forestry involves a complex network of interactions between stakeholders. Conservation rather than social motives drive more organisations active in villages. Bonding social capital is important for Initiating the community forest process. NGOs bridge village-level activities and the organisational network. Abstract: Governance of the environment and natural resources involves interests of multiple stakeholders at different scales. In community-based forest management, organisations outside of communities play important roles in achieving multiple social and ecological objectives. How and when these organisations play a role in the community-based forest management process remains a key question. We applied social network analysis to a case study in Indonesian Borneo to better understand the evolution of interactions between organisational actors, and with communities. NGOs featured most prominently in initiating the permit process, implementing management, and providing other support activities, while also being well-connected to donors and government actors. The network configurations indicated significant cooperation among organisations when initiating the community forest process, while bridging between village and organisational levels characterised all stages of the community forest process. While community-based forest management often evokes images of grassroots efforts and broad local capacity to manage forests, reality shows a more dynamic and heterogeneous picture and broader involvement of different actor types and motivations in Indonesia. These findings can be applied to other countries implementing and expanding their decentralised forest policies.